Pelatihan Pengenalan SFA (Stochastic Frontier Analysis) Dengan Software Frontier 4.1c di Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura - Hastarini Dwi Atmanti; Crisanty Sutristyaningtyas Titik; Ris Yuwono Yudo Nugroho (Yayasan Sagita Akademia Maju, 2025)
This community service aims to provide training for students and lecturers of the Faculty of Economics and Business, Universitas Trunojoyo Madura, specific training on using the Frontier 4.1c software. The software is used to analyze problems related to efficiency measurement using a stochastic approach, commonly referred to as SFA (Stochastic Frontier Analysis). The training is conducted online. The participants are equipped with knowledge of production theory, basic SFA theory, inputting data and the running of the data, as well as result interpretation. The method used in this community service is EAR (Educational Action Research) to address the issue of participants' lack of understanding of SFA. This training benefits participants, most of whom are students, by providing them with proficiency in using software for efficiency measurement using the stochastic (SFA) approach.